Implementation of Maritime Environmental Pollution Prevention Policy at The Manado Harbormaster and Port Authority Office - Manampiring, Yulita M.; Langkai, Jeane E.; Mokat, Yetty E. H. (Technium Social Sciences Journal, 2024)
This research aims to describe, analyze, and interpret the evaluation of the implementation of Minister of Transportation Regulation Number 29 of 2014 concerning Prevention of Maritime Environmental Pollution at the Manado Harbormaster and Port Authority (KSOP) office. This research uses qualitative methods, because qualitative research places more emphasis on the process of searching for meaning, revealing the meaning behind the phenomena that appear in the research, with the aim that the problems studied are more comprehensive, in-depth, natural, and real, and without much interference from researchers to the facts that emerge. The results of the research reveal that there are several ships that repeatedly apply for temporary pollution certificates. According to regulations or rules, it is not justified to extend pollution certificates repeatedly, but this is done based on aspects of social and economic impacts which if not done will result in delays. the ship's departure because it cannot be given a Sailing Approval Letter (SPB) if the ship does not have a temporary or permanent pollution certificate. This of course creates losses for the ship owner and will have a social impact on everyone involved on the ship, for example, the ship's crew. For this reason, an extension of the temporary prevention certificate is given with various other considerations, both administrative and technical, as well as providing advice and suggestions to the ship owner to immediately complete the lack of documents that must be fulfilled to obtain a permanent prevention certificate.